1975
DOI: 10.1111/j.1432-1033.1975.tb02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat‐Liver Cholesterol 7α‐Hydroxylase

Abstract: The establishement of the circadian rhythm of cholesterol 7a-hydroxylase activity requires protein and RNA synthesis. The spontaneous decrease of the enzymic activity, at the end of the night, allows us to evaluate a half-life time of about two hours. The half-life time goes up to about four hours when the enzymatic activity decay is measured following cycloheximide administration. This difference suggests that an active mechanism is involved in the control of the enzyme degradation. The daily variation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 34 publications
0
22
1
1
Order By: Relevance
“…Previous studies have also reported that the diurnal rhythm of C7␣OH activity is attenuated or abolished in Hx rats (42,43). This finding could not be confirmed in the present study, however.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have also reported that the diurnal rhythm of C7␣OH activity is attenuated or abolished in Hx rats (42,43). This finding could not be confirmed in the present study, however.…”
Section: Discussioncontrasting
confidence: 57%
“…Cholesterol 7a-hydroxylase is different from most of the liver microsomal mixed-function oxidases in certain aspects. For example it exhibits a marked diurnal rhythm in a similar way to hydroxymethylglutaryl-CoA reductase [9]. The interruption of the enterohepatic circulation of bile salts by the establishment of a total biliary fistula, or the oral administration of a bile salt-sequestering agent such as cholestyramine causes a several-fold increase in cholesterol 7a-hydroxylase activity without causing any change in the total hepatic Etzzymes.…”
mentioning
confidence: 99%
“…Compared to the enzyme apparent K,,, (110 x M) [8,35] the apparent Ki for pregnenolone (80 x M) pregnenolone acetate (60 x M), 7-dehydrocholesterol (25 x M) and 7-oxocholesterol (7 x M) demonstrated that these molecules have a stronger affinity for the enzyme than the theoretical substrate itself. The fact that other molecules very closely related to cholesterol, like most of its esters or the main biliary acids, do not inhibit significantly cholesterol 7a-hydroxylase, suggests that (a) the enzyme active site has very specific structural requirements, (b) certain steroids in low concentration might play a role in the regulation of the enzyme, (c) hormonal steroids endogenously produced or administered for a therapeutic effect could interfere with cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%